Implementation of Reproductive Organs Care among Bachelor Students of Nursing - Yanti Srinayanti; Ade Fitriani; Lilis Lismayanti; Susi Sulistiawati (Inspirasi Foundation, 2021)
Background: Reproductive health is a state of complete physical, mental and social health, not only free from disease or disability in all aspects related to the reproductive system, its functions and processes. Reproductive health is related to the cleanliness of the organs. It is very important to keep the reproductive organs clean, it is also necessary to pay attention to how to maintain and care for them properly and correctly, especially in women, because women have a reproductive system that is sensitive to disease. Objective: This study aimed to analyze the implementation of reproductive organ care for undergraduate nursing students of STIKes Muhammadiyah Ciamis. Methods: This study used an analytic survey research with a research design used was purposive sampling with the type of research design using descriptive quantitative. The population in this study were second and third level students of the S1 Nursing Study Program of STIKes Muhammadiyah Ciamis. Samples were taken as many as 55 respondents using purposive sampling technique. The data collected consisted of primary data obtained through questionnaire sheets and direct observation and statistical analysis using number and percentage. Results: The results of this study showed that the implementation of reproductive organ care by undergraduate nursing students in the highest category was carried out by 32 people (58.18%), and the category was not carried out by 23 people (41.82 %). Conclusion: in this study, the highest category of reproductive organ care was carried out by 32 people (58.2%). Therefore, this treatment is very important to keep the health of the reproductive organs.